Mediation as a new solution for solving conflicts on financial markets - Broszkiewicz, Magdalena (Mediacja jako nowy sposób rozwiązywania konfliktów na rynkach finansowych, 2017)
The development of the financial market is usually described in terms of new instruments, institutions or integration groups. Aspects often result in a delayed increase in market participants’ confidence, as the learning process of innovation is necessary. In the meantime, the anti-conflict mediation procedure, conflicts of diverse background, allow the parties to compromise and work out agreements that also benefit the entire financial market. The article attempts to argue for the hypothesis emphasizing the role of mediation in improving the level of financial market functioning and the level of investment attractiveness of financial market players. The article shows mediation as a solution to potential conflicts, as described in the current theory of economics and finance, as well as to problems in reality. The research was based on the literature of the subject and on mediation practices on the Polish financial market. The mediation procedure present on the Polish financial market is used especially in the insurance and banking sectors as well as in public finances, contributing to raising the level of trust of the individual entities
Nauki o Finansach = Financial Sciences, 2017, Nr 4 (33), s. 22-34
Keywords: mediation; financial markets; capital markets; information asymmetry; mediacja; rynki finansowe; rynki kapitałowe; asymetria informacji